2013
DOI: 10.1093/gerona/gls337
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Dietary Restriction and Exercise on Lower Extremity Tissue Compartments in Obese, Older Women: A Pilot Study

Abstract: DR + E preserved lower extremity muscle size and function and reduced regional lower extremity adipose tissue. Although the magnitude of reduction in adipose tissue was greater in the thigh than the calf region, post hoc analyses demonstrated that reductions in calf SAT and IMAT were associated with positive adaptations in physical function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 36 publications
1
29
0
1
Order By: Relevance
“…Dietary weight loss can directly impact physical function by improving muscle quality and reducing intramuscular adipose tissue(Manini, Buford, Lott, Vandenborne, Daniels, Knaggs, Patel, Pahor, Perri, and Anton 2014) and decreasing joint load (Messier, Loeser, Miller, Morgan, Rejeski, Sevick, Ettinger, Pahor, and Williamson 2004). Weight reduction in overweight individuals can also impact physical function indirectly by reducing pain(McCarthy, Bigal, Katz, Derby, and Lipton 2009) and fatigue.…”
Section: Discussionmentioning
confidence: 99%
“…Dietary weight loss can directly impact physical function by improving muscle quality and reducing intramuscular adipose tissue(Manini, Buford, Lott, Vandenborne, Daniels, Knaggs, Patel, Pahor, Perri, and Anton 2014) and decreasing joint load (Messier, Loeser, Miller, Morgan, Rejeski, Sevick, Ettinger, Pahor, and Williamson 2004). Weight reduction in overweight individuals can also impact physical function indirectly by reducing pain(McCarthy, Bigal, Katz, Derby, and Lipton 2009) and fatigue.…”
Section: Discussionmentioning
confidence: 99%
“…For example, increased fat infiltration into muscle bundles can lead to the accumulation of intermuscular adipose tissue, 62,63 which has been found to adversely affect mitochondrial function 64,65 and insulin signaling. 66 Converging evidence suggests that reductions in mitochondrial function have a pivotal role in the pathogenesis of muscle degradation 67,68 and cardiometabolic disorders.…”
Section: Discussionmentioning
confidence: 99%
“…3,19 Specifically, this cutoff may indicate an increased risk of abnormal gait (including declines in gait speed and step length) or falls. 36,37,38 Reduced torque from the gastrocnemius and soleus may diminish one’s ability to slow the forward progression of the body about the ankle when recovering from a perturbation. 38 Indeed, Landi et al reported that individuals who are sarcopenic are at 3.23 times higher risk for falls than individuals without sarcopenia regardless of age, gender, BMI, or secondary impairments (e.g., diabetes, stroke).…”
Section: Discussionmentioning
confidence: 99%
“…7,8,11 Moreover, the reliance on measures of grip strength fails to characterize muscle function in the lower extremity (particularly calf muscles), which is severely affected by type 2 diabetes + PN, and is more closely associated with physical function than thigh or upper extremity musculature. 12 Measures of lower extremity strength and functional power, therefore, may provide a more accurate basis for sarcopenic classification, particularly in individuals with diabesity. Additionally, because changes in muscle composition are critical to muscle quality, and excess IMAT infiltration reduces muscle quality and performance, we hypothesized that there may be relationships between leg IMAT accumulation and sarcopenic decline, particularly in diabesity – a condition characterized by progressive IMAT accumulation and accelerated sarcopenia.…”
Section: Introductionmentioning
confidence: 99%